Acute outcomes of isolated cerebral contusions in children with Glasgow Coma Scale scores of 14 to 15 after blunt head trauma. Issue 5 (May 2015) - Varano, Paul; Cabrera, Keven I.; Kuppermann, Nathan; Dayan, Peter S.
<x xml:space="preserve">Abstract</x> BACKGROUND Little data exist to guide the management of children with cerebral contusions after minor blunt head trauma. We therefore aimed to determine the risk of acute adverse outcomes in children with minor blunt head trauma who had cerebral contusions and no other traumatic brain injuries on computed tomography (i.e., isolated cerebral contusions). METHODS We conducted a secondary analysis of a public use data set originating from a prospective cohort study performed in 25 PECARN (Pediatric Emergency Care Applied Research Network) emergency departments of children younger than 18 years with blunt head trauma resulting from nontrivial injury mechanisms and with Glasgow Coma Scale (GCS) scores of 14 or 15. In this analysis, we included only children with isolated cerebral contusions. We defined a normal mental status as a GCS score of 15 and no other signs of abnormal mental status. Acute adverse outcomes included intubation longer than 24 hours because of the head trauma, neurosurgery, or death from the head injury. RESULTS Of 14, 983 children with GCS scores of 14 or 15 who received cranial computed tomography scans in the parent study, 152 (1.0%; 95% confidence interval, 0.8–1.2%) had cerebral contusions, of which 54 (35.8%) of 151 with available data were isolated. The median age of those with isolated cerebral contusions was 9 years (interquartile range, 1–13); 31 (57.4%) had a normal mental status. Of 36 patients with available data on isolated cerebral contusion size, 34 (94.4%) were described as small. 43 (79.6%) of 54 patients with isolated cerebral contusions were hospitalized, including 16 (29.6%) of 54 to an intensive care unit. No patients with isolated cerebral contusions died, were intubated longer than 24 hours for head trauma, or required neurosurgery (95% confidence interval for all outcomes, 0–6.6%). CONCLUSION Children with small isolated cerebral contusions after minor blunt head trauma are unlikely to require further acute intervention, including neurosurgery, suggesting that neither intensive care unit admission nor prolonged hospitalization is generally required. LEVEL OF EVIDENCE Epidemiologic study, level IV.